Differential Regulation of Hyaluronan Synthesis by Three Isoforms of Hyaluronan Synthases in Mammalian Cells - Jie Wang; Zhikun Wu; Longtao Cao; Feng Long (Biomolecules)
Hyaluronan (HA) is one of the crucial components of the extracellular matrix in vertebrates and is synthesized by three hyaluronan synthases (HASs), namely HAS1, HAS2, and HAS3. The low expression level of HASs in normal keratinocytes and other various types of cells presents a recognized challenge, impeding biological and pathological research on their localization. In this study, the human proteins HAS1, HAS2, and HAS3 with fused maltose-binding protein (MBP) tags were successfully expressed at high levels and purified for the first time in HEK293F cells. The enzymatic properties of the three HAS proteins were further characterized and compared. A pulse-field gel electrophoresis analysis of the size distribution of the hyaluronan generated in vitro by the membrane proteins demonstrated that the three HAS isoforms generate HA polymer chains at different molecular masses. Kinetic studies demonstrated that the three HAS proteins differed in their catalytic efficiency and apparent Km values for the two substrates, UDP-GlcA and UDP-GlcNAc. Furthermore, the cellular hyaluronan secretion by the three isoenzymes was evaluated and quantified in the HEK 293T cells transfected with GFP-tagged HAS1-GFP, HAS2-GFP, and HAS3-GFP using an ELISA assay. These findings enhance our understanding of the membrane protein HASs in mammalian cells.